Retinoblastoma growth suppressor and a 300-kDa protein appear to regulate cellular DNA synthesis. - Howe, J A (1990)
Previous work has suggested that oncogenic transformation by the E1A gene products of adenovirus type 5 may be mediated through interactions with at least two cellular proteins, the 105-kDa product of the retinoblastoma growth suppressor gene (p105-Rb) and a 300-kDa protein (p300). By using viral mutants, we now show that the induction of cellular DNA synthesis in quiescent cells by E1A differs from transformation in that E1A products induce synthesis if they are able to bind to either p105-Rb or p300, and only mutant products that bind to neither are extremely defective. These results suggest that p105-Rb and p300 (or cellular proteins with similar E1A-binding properties) provide parallel means by which DNA synthesis can be regulated.